Evaluation of Extra-Cranial Carotid Arteries by Digital Subtraction Angiogram (DSA) in Stroke Patients in a Tertiary Care Hospital (Medicine Today, 2022)
Introduction: Carotid artery stenosis is one of the important causes of ischemic stroke. This may be diagnosed by Doppler Ultrasound and Digital Subtraction Angiogram (DSA) both of which have some advantages and disadvantages.Objective: The aim of this study was to assess extra-cranial carotid artery with the help of DSA among patients of ischemic stroke and transient ischemic attack (TIA).Materials and Methods: This observational cross sectional study was conducted in the Department of Neurology in Bangabandhu Sheikh Mujib Medical University (BSMMU) Dhaka from July 2013 to June 2015 for a period of two years. This study included a total of 50 patients. Diagnostic performance test of DSA was done at 50%, 50-69%, 70-99%, 100% cut off point of stenosis of right internal carotid artery (RICA) and Left internal carotid artery (LICA).Results: The mean age of cases was 61 ± 11.42 years. Out of 50 vessels, maximum cases were diagnosed as